2019
DOI: 10.1088/1755-1315/292/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Kefir Produced from Red Rice Milk by Lactobacillus bulgaricus and Candida kefir Starter

Abstract: Kefir is a dairy product commonly fermented by bacteria and yeasts. One of the potential vegetable milk materials to be used in kefir production is milk from red rice. Studies of fermentation of milk from red rice to produce kefir are barely found. This study aimed to determine the nutrient content of red rice milk kefir fermented using mixed of microorganisms, Lactobacillus bulgaricus and Candida kefir, in various concentrations of 3%, 9%, and 15%, respectively. The content of carbohydrate, fat, protein, wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
5
2
1
Order By: Relevance
“…Table 2 shows that moringa leaf powder does not affect the ash produced (P>0.05). Ash is the percentage of mineral content in a product (28). The average ash in this study is 9.88%, which is higher than goat milk kefir in two previous findings, namely 0.77% (19) and 5.24% (20), and 5.43% in kefir plus ginger extract (21).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…Table 2 shows that moringa leaf powder does not affect the ash produced (P>0.05). Ash is the percentage of mineral content in a product (28). The average ash in this study is 9.88%, which is higher than goat milk kefir in two previous findings, namely 0.77% (19) and 5.24% (20), and 5.43% in kefir plus ginger extract (21).…”
Section: Resultscontrasting
confidence: 54%
“…At last, this study found that Moringa leaf powder does not affect (P>0.05) the level of carbohydrate (Table 2), which is 5.019% on average. This level of carbohydrate was not significantly different from previous findings, i.e., 5.53% (29), 5,08% (30) and 3.95% (28). Similarly, Hardiansyah (29) stated that carbohydrate analysis investigates the content of carbohydrates (including fiber) through calculation instead of analysis.…”
Section: Resultscontrasting
confidence: 45%
“…The alcohol cyclobutanol was detected at 2.5 % inoculum with 27.5 °C and 4 % inoculum at 23.9 °C, while the alcohol 2-undecanol was only detected at 2.5 % inoculum and 27.5 °C (Table 2). The increasing content of alcohol in the kefir was directly proportional to the increase in starter quantity (Sulistyaningtyas et al, 2019). Thus, the number of starters used had potential to alter alcohol content in kefir.…”
Section: Alcoholsmentioning
confidence: 99%
“…El uso de cultivos comerciales puede normalizar la producción comercial de kéfir, si la selección de especies y cepas de levaduras y bacterias se lleva a cabo con precisión y cuidado, permitiendo así la producción de una bebida "tipo kéfir" con un sabor aceptable y buenas propiedades de conservación (Simova et al, 2002;Sulistyaningtyas et al, 2019). Sin embargo, es posible que la bebida no presente las mismas propiedades terapéuticas y probióticas presentes en el kéfir tradicional (Rattray & O'Connell, 2011).…”
Section: Producciónunclassified